Molecular characteristics and alterations during early development of the human vagina - Fritsch, Helga (Blackwell Science Inc, 2012)
Unresolved questions remain concerning the derivation of the vagina with respect to the relative contributions from the Müllerian ducts, the urogenital sinus, and the Wolffian ducts. Recent molecular and cellular studies in rodents have opened up a large gap between the level of understanding of vaginal development in mice and understanding of human vaginal development, which is based on histology. To compare the findings in mice with human vaginal development and to address this gap, we analysed molecular characteristics of the urogenital sinus, Wolffian ducts, and Müllerian ducts in 8–14-week-old human specimens using immunohistochemical methods. The monoclonal antibodies used were directed against cytokeratin (CK) 14, CK19, vimentin, laminin, p63, E-cadherin, caspase-3, Ki67, HOX A13, and BMP-4. The immunohistochemical analysis revealed that, during weeks 8–9, the epithelium of the Müllerian ducts became positive for p63 as p63-positive cells that originated from the sinus epithelium reached the caudal tip of the fused Müllerian ducts via the Wolffian ducts. The lumen of the fused Müllerian ducts was closed by an epithelial plug that contained both vimentin-positive and vimentin-negative cells. Subsequently, the resulting epithelial tube enlarged by proliferation of basal p63-positive cells. The first signs of squamous differentiation were detected during week 14, with the appearance of CK14-positive cells. According to our results, all three components, namely, the urogenital sinus, Wolffian ducts, and Müllerian ducts, interacted during the formation of the human vagina. The sinus epithelium provided p63-positive cells, the Wollfian ducts acted as a ‘transporter’, and the Müllerian ducts contributed the guiding structure for the vaginal anlagen. Epithelial differentiation began at the end of the period studied and extended in a caudo-cranial direction. The present study is one of the first to provide up-to-date molecular correlates for human vaginal development that can be compared with the results of cell biological studies in rodents.